Optimizing women's entrepreneurship to enhance family domestic income: a case study of female entrepreneurs in Batam, Indonesia - Tiurniari Purba; David Humala Sitorus; Hermaya Ompusunggu (Journal of Innovation and Entrepreneurship)
Abstract The phenomenon of female entrepreneurship has become a prominent economic dynamic, especially in Batam, Indonesia. Research that specifically addresses the socio-economic and cultural nuances of Batam is still limited. This gap highlights the limited access to quality employment opportunities for the majority of Batam’s female population. The purpose of this study is to analyze and highlight the important role of female entrepreneurship in increasing household income in the unique socio-economic context of Batam. We designed the study using a mixed method, combining quantitative and qualitative approaches. This study employs PLS–SEM or partial least squares structural equation modeling. We conducted qualitative data analysis using NVivo software. Social networks and support systems serve as mediators in the relationship between women’s entrepreneurship and family income. Women's entrepreneurship raises family income and calls for supportive measures to empower women entrepreneurs, ultimately contributing to economic and social progress in Batam. This study contributes to the literature on household income determinants by demonstrating the importance of access to capital.